The Influence of using Audio Visual Media and the Professional Competence of Religious Education Teachers on Learning Motivation - Melina Manalu; Sudirman Lase; Robert Juni Tua Sitio (Formosa Journal of Science and Technology, 2023)
The aim of the research is to determine the influence of using audio-visual media on student learning motivation, the influence of PAK teachers' professional competence on students' learning motivation, and the influence of using audio-visual media and PAK teachers' professional competence together on students' learning motivation. Research with a quantitative descriptive inferential approach. The population of all class X students at SMA Negeri 1 West Sorkam for the 2023/2024 academic year is 300 people. The sample was determined using a random sampling technique of 15%, namely 45 people. The research was analyzed in the following steps: 1) testing the analysis requirements for the relationship between X1 and Y, obtained rcount=0.634>rtabel=0.294, the relationship between 2) Hypothesis testing shows that H0 is rejected and Ha is accepted, namely that there is a positive and significant influence of the use of audio-visual media on the learning motivation of class There is a positive and significant influence between the professional competence of Religious Education teachers on the learning motivation of class.